Pengaruh Kecerdasan Emosional Terhadap Creative Thinking Skills Siswa Dalam Pembelajaran Biologi - Nita Ayuspinta (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This research aims to prove the influence of emotional intelligence on the creative thinking abilities of class XI MIPA students in Biology learning at SMA Negeri 15 Bone. The research used is quantitative research with One-Group Pre-test and Post-test design research type. The total population consists of 6 classes with the research sample used, namely class XI MIPA 4 SMA Negeri 15 Bone with a total of 30 students. Sampling was carried out using purposive sampling technique. The data collection technique used is presenting pre-test, post-test and documentation questions. Hypothesis testing was carried out using the t-test or paired sample pre-test and post-test, obtaining a significance value of less than 0.05, namely 0.00 where sig (2-tailed) < 0.05. Because the significance value is <0.05, it can be concluded that between the pre-test and post-test data there is a significant influence on the differences in treatment for each variable. Thus, research shows that the use of learning models that involve emotional intelligence influences students' creative thinking abilities in biology learning.